Rethinking Pedagogy in the Digital Age: Analyzing the Effectiveness of E-Learning Strategies in Higher Education - Sain, Zohaib Hassan; Baskara, Risang; Vorfi Lama, Alma (Ali Institute or Research and Publication, 2024)
This paper delves into the multifaceted challenges posed by the intersection of infrastructure, education, and technology integration in the context of enriching the learning experience. Rather than displacing educators, technology is positioned as a valuable tool to augment learning, necessitating a nuanced approach. Universities are confronted with the complexities of E-Learning, prompting the adaptation of course structures to accommodate diverse educational needs. Consequently, educators adjust teaching styles, leading to heightened workloads that demand proactive management. The impact of E-Learning extends beyond individual classrooms, challenging traditional university frameworks and compelling institutions to reconsider physical facilities and lecture-centric methodologies. Anticipated benefits of E-Learning must be balanced with a thorough evaluation of its implications. Despite the widespread adoption of technology, some implementations need to be more actively engaging learners, functioning more as content repositories than dynamic learning environments. This underscores the importance of establishing a robust pedagogical foundation when embracing E-Learning, ensuring that technology aligns with, rather than supersedes, student progress and engagement objectives.